CYTOTOXICITY OF CHLOROFORM EXTRACT OF WALTHERIA INDICA L. LEAF - Gopi Krishna, *Sirimal; Sudarsanam, Gudivada (International Journal of Ayurveda and Pharma Research, 2015)
India has the richest bio-resource of medicinal plants that have long life history of application in the treatment of diseases from the ancient times. The drugs that are obtained from the medicinal plants have been well favored by the people because of its treatment efficacy which is less when compared to the modern drugs but causes lesser side effects. This advantage lead the research field of pharmacy to discovery of the active constituents that are responsible for causing the pharmacological action on human body. The active constituents from the medicinal plants are more effective and do not cause any side effects. This study has been made to investigate the cytotoxic effect of chloroform extracts of Waltheria indica leaves on cervical cancer cells. Extracts were studied for their toxicity by MTT assay, Trypan blue dye exclusion assay, cell viability was studied by LDH assay and Apoptosis was measured by DNA fragmentation assay. The extract screened for phytochemical analysis was found to contain bioactive compounds like carbohydrates, glycosides, saponins, phenolic compound and triterpenoids were present..The cytotoxicity study clearly showed the dose dependent cytotoxic effect of extract in HeLa cell line with an CTC50 of 103.33±5.77 for MTT assay and 90.00 for Trypan blue dye exclusion assay. The LDH leakage was observed in a dose dependent manner with an LDH IU/mg of total protein of 36.18. The dying cells showed characteristics of apoptosis such as, DNA fragmentation. The data in the present study clearly demonstrated cytotoxic effects of extracts on human cervical cancer cells.